Google Sites: Inovasi Pembelajaran Digital untuk Meningkatkan Kemampuan Berpikir Analitis Siswa pada Pembelajaran Al-Qur’an dan Hadits - Ni'mah, Zahrotun (PT. Pusmedia Group Indonesia, 2025)
The development of information and communication technology has brought significant changes in the field of education, marked by the integration of digital technology into the learning process. Digital-based learning encourages students to think analytically. The development of Google Sites as a digital learning medium serves as a bridge to enhance students’ analytical thinking skills, particularly regarding the dangers of student brawls, alcohol consumption, and drug abuse, enabling them to avoid such behaviors. This study aims to examine the practicality and effectiveness of the developed Google Sites digital learning media. The research was conducted at MA Darul Huda Mlagen Rembang using a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The practicality and effectiveness of the Google Sites digital learning media were tested using a randomized control group pretest-posttest design, with class XI MIPA students as the experimental group and class XI IPS students as the control group. Data were collected through observation, questionnaires, and tests administered before and after the use of Google Sites. The data were analyzed using both descriptive quantitative and qualitative methods to assess practicality, and statistical tests (t-tests) to evaluate the effectiveness of the developed digital learning media. The results of the study indicate that the Google Sites digital learning media: (1) has a practicality level of 84%, indicating it is highly suitable for use in Islamic Religious Education, particularly in addressing the issues of student brawls, alcohol, and drugs; and (2) is effective in enhancing students’ analytical thinking skills in Qur’an and Hadith learning, with an N-Gain score index of 77.79%. Keywords: Google Sites; Digital Learning; Analytical Thinking; Al-Qur’an and Hadith